Consumer Protection in E-Commerce Transactions From the Perspective of Fiqh Jinayah - Sumardi Efendi; Aulil Amri; Sufrizal Sufrizal; Tabsyir Masykar (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2025)
The rapid development of e-commerce transactions in the digital era has brought significant convenience to society; however, it has also generated various legal issues that potentially harm consumers, such as fraud, lack of transparency of information, gharar (uncertainty), and the misuse of personal data. This study aims to analyze the concept of consumer protection in e-commerce transactions from the perspective of fiqh jinayah and to examine its relevance in strengthening consumer legal protection. The research employs a qualitative method with a normative approach through library research by examining sources of Islamic law, fiqh principles, as well as scholarly literature and regulations related to consumer protection and electronic transactions. The findings indicate that fiqh jinayah categorizes violations in e-commerce transactions as unlawful acts (jarīmah), particularly those involving tadlīs (deception), gharar, and harmful conduct (ḍarar), as they contradict the principles of justice and the protection of property (ḥifẓ al-māl). Furthermore, fiqh jinayah provides a flexible and contextual mechanism of ta‘zīr sanctions aimed at creating a deterrent effect, ensuring preventive protection, and promoting restorative justice for affected consumers. This study concludes that integrating the principles of fiqh jinayah with positive law can strengthen a fair, ethical, and Islamic value-based system of consumer protection in e-commerce.